Identification of bacteria associated with holothuria (Mertensiothuria) leucospilota from Pangkor Island - Lutfi F.N.M.; Rehan M.M.; Kamarudin K.R.; Che Zahri M.Z.; Noor H.M.; Radzi S.M. (Malaysian Society of Applied Biology, 2024)
Indexed by SCOPUS